Analysis of Students' Initial Ability in Biopolymer Material - Pratiwi, Alfira Julian; Kurniawan, Ekin Dwi Arif; Ridho, Dimas (Holistic Science, 2024)
This study aims to identify students' initial abilities in biopolymer materials as a basis for developing learning designs. This study uses a content analysis method, with participants being fourth-semester students in one of the Chemistry Education study programs, at a state university in West Java. The instrument used in this study was a descriptive test consisting of 13 questions. The results of the Initial ability data analysis showed that overall, it was identified that 41% of students had an Initial ability understanding with a sufficient category, 33% of students had a poor category, 23% of students had a good category and 3% of students had an initial ability understanding with an outstanding category. Based on these findings, several interventions are suitable as references in developing didactic designs, such as displaying learning videos related to the manufacture of simple bioplastics, graphs of development and annual production costs of bioplastics, images of bioplastic applications in various fields, and infographics related to the decomposition process and the benefits of sustainability of bioplastics.